Towards an Expansive Capital: Perspectives on Community-Based Impact Investment and the Racial Wealth Gap - Ramesh, Rahul. (Tufts University. Tisch Library., 2024)
Thesis (M.A.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shomon Shamsuddin.; Committee: Rebecca Shakespeare.; Keywords: Urban planning, and Entrepreneurship.